Comparison of reconstructive techniques after acetabular resection for pelvic chondrosarcoma. (1st February 2021) - Houdek, Matthew T.; Wunder, Jay S.; Abdel, Matthew P.; Griffin, Anthony M.; Hevesi, Mario; Rose, Peter S.; Ferguson, Peter C.; Lewallen, David G.
Abstract : Aims: Hip reconstruction after resection of a periacetabular chondrosarcoma is complex and associated with a high rate of complications. Previous reports have compared no reconstruction with historical techniques that are no longer used. The aim of this study was to compare the results of tantalum acetabular reconstruction to both historical techniques and no reconstruction. Methods: We reviewed 66 patients (45 males and 21 females) with a mean age of 53 years (24 to 81) who had undergone acetabular resection for chondrosarcoma. A total of 36 patients (54%) underwent acetabular reconstruction, most commonly with a saddle prosthesis (n = 13; 36%) or a tantalum total hip arthroplasty (THA) (n = 10; 28%). Mean follow-up was nine years (SD 4). Results: There was no difference in the mean age (p = 0.63), sex (p = 0.110), tumour volume (p = 0.646), or type of resection carried out (p > 0.05) between patients with and without reconstruction. Of the original 66 patients, 61 (92%) were ambulant at final follow-up. There was no difference in the proportion of patients who could walk in the reconstruction and 'no reconstruction' groups (p = 0.649). There was no difference in the mean Musculoskeletal Tumor Society (MSTS) score between patients who were reconstructed and those who were not (61% vs 56%; p = 0.378). Patients with a tantalum THA had a significantly (p = 0.015) higher mean MSTS score (78%) than those who were reconstructed with a saddle prosthesis (47%) or who had not been reconstructed (56%). Patients who had undergone reconstruction were more likely to have complications (81% vs 53%; p = 0.033). Conclusion: Reconstruction after resection of the acetabulum is technically demanding. In selected cases, reconstruction is of benefit, especially when reconstruction is by tantalum THA; however, the follow-up for these patients remains mid-term. When not feasible, patients with no reconstruction have an acceptable functional outcome. Level of Evidence: Level III Therapeutic. Cite this article: Bone Joint J 2021;103-B(2):391–397.